1984
DOI: 10.1149/1.2115961
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Interface Between Two Immiscible Electrolytes in the Presence of Proteins

Abstract: The influence of adsorbed proteins on electrochemical properties of the nitrobenzene‐aqueous interface has been investigated using cyclic voltammetric and impedance techniques. Upon addition of 4 μg/ml ovalbumin cyclic voltammetric normalΔEP values for Cs+ transfer shifted from nearly temperature independent reversible values to more temperature‐dependent irreversible values. These effects were especially pronounced at lower temperatures and suggested formation of a surface film. The cyclic voltammetry of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 2 publications
1
23
0
Order By: Relevance
“…Early studies of the behaviour of proteins at the ITIES were reported by Vanysek and colleagues, [34][35][36] in which proteins were examined within a programme to assess the behaviour of biological molecules in general. In these studies, the main findings were that proteins such as ovalbumin, colicine E 3 , and bovine serum albumin (BSA) form adsorbed layers at the ITIES.…”
Section: Early Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies of the behaviour of proteins at the ITIES were reported by Vanysek and colleagues, [34][35][36] in which proteins were examined within a programme to assess the behaviour of biological molecules in general. In these studies, the main findings were that proteins such as ovalbumin, colicine E 3 , and bovine serum albumin (BSA) form adsorbed layers at the ITIES.…”
Section: Early Studiesmentioning
confidence: 99%
“…These layers were studied by cyclic voltammetry and impedance methods and revealed that simple ion transfer reactions were inhibited (e.g. transfer of Cs + across the ITIES between water and NB), 35 as shown in Fig 2. Here, the experimental arrangement was that of a large interface (i.e. millimetre or centimetre in scale) set up in a glass cell containing two counter electrode and two reference electrodes.…”
Section: Early Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst these, electrochemistry at polarised liquid|liquid interfaces has been used for the investigation of non-redox electrochemistry [2,3] and electroanalytical determination [4] of a range of ions. Recently, a variety of large polycationic molecules have been studied at the liquid|liquid interface, EC09-2006, revised 16Dec2009 2 including dendrimers [5], peptides [6] and proteins [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. We have recently investigated the electrochemical behaviour of haemoglobin [15][16][17], insulin [18] and lysozyme [19] at the liquid | liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…[25c, 100] The first investigations of proteins at the ITIES dates from the 1980s, when Vanysek and colleagues [101] reported the interfacial adsorption of ovalbumin, which was shown to alter a simple IT process. Subsequently, there were few studies of proteins undertaken, in comparison to studies of small molecules.…”
Section: Detection Of (Bio)macromoleculesmentioning
confidence: 99%